HUBUNGAN ANTARA COPING STRATEGY DENGAN KENAKALAN PADA REMAJA AWAL - Nila Ainu Ningrum (University of Merdeka Malang, 2012)
Abstract This study aims to determine whether there is a relationship between coping strategy with delinquency in the orpanage of Arrahmah Kediri . This research is done in the early adolescents who live in orphanages Arrahmah-kediri with the number of subjects of research as much as 60 teenagers. Results of research indicate that the coping strategy has a negative relationship with juvenile delinquency. Coping strategy in the early adolescents in the orphanage has a relationship with juvenile delinquency. Relations the coping strategy with juvenile delinquency is not significant. Keywords: coping strategy, ,juvenile delinquency, adolescence